Masala stored in empty bottles - Mumbai Archive Project Team (Jio Institute, 2024)
Bottle masala gets its quirky name because it was traditionally stored in empty beer bottles. The airtight bottles preserved the original aroma and flavour of the masala and kept out moisture.